AB0753 THE CONTRIBUTION OF JOINT SYMPTOMS, ENTHESITIS, SKIN AND NAIL PSORIASIS (PSO) TO MINIMAL DISEASE ACTIVITY (MDA) ACHIEVEMENT IN PSORIATIC ARTHRITIS (PSA) PATIENTS (PTS). EFFECT OF TOFACITINIB TREATMENT. DATA FROM REAL CLINICAL PRACTICE. (2nd June 2020) - Chamurlieva, M.; Loginova, E.; Gubar, E.; Korsakova, Y.; Glukhova, S.; Korotaeva, T.
Abstract : Background: PsA is an inflammatory arthritis associated with skin and nail PsO. The treatment target of PsA is MDA. In order to achieve MDA it is necessary to significantly improve musculoskeletal (MSK) symptoms, skin symptoms and patient-reported outcomes (PROs). In RCT it has been recently demonstrated that targeting both joint and skin symptoms is very important in achieving optimal improvement in health-related quality of life [1]. However, there is not enough data from clinical practice. Tofacitinib (TF) is an oral Janus kinase inhibitor approved for the treatment of PsA pts. Objectives: to study the influence of joint, enthesitis, skin and nail symptoms on MDA achievement in active PsA (pts) treated with TF for 6 months (mo). Methods: 41pts (M/F=24(58.5%)/17(41.5%) with active PsA fulfilling the CASPAR criteria, were included after signing consent participation forms. Mean age 42.4±10.3 years (yrs), median (Me) PsA duration 72 [35;120] mo, PsO duration 192 [98;312] mo, PASI 14.5 [7;23.8], DAPSA 44.2 [37.8;55.3]. Pts were treated with TF 5 mg twice daily. At baseline (BL) and over a period of 6 mo of therapy PsA activity was evaluated by Tender Joint Count (TJC68), Swollen Joint Count (SJC66); PGA, physician global assessment by Visual Analog Scale (VAS), DAPSA. Enthesitis was evaluated by LEI (Leeds Enthesial Index) plus Plantar Facia (PF); PROs were measured by PtGA VAS, PtPain VAS, HAQ. PsO were measured by PASI/BSA (%). The presence/absent of Nail PsO was evaluated. The number of pts (NPts) who reached MDA (5/7: TJC≤1, SJC≤1, PASI≤1/BSA≤3, PtPainGA≤15, PtGA≤20, HAQ≤0, 5, enthesitis count≤1) was calculated. M±SD, Me[Q25;Q75], %, Pearson-χ 2, OR 95% (CI) were performed. All p<0.05 were considered to indicate statistical significance. Results: At BL mean TJC/SJC/PtPainGA/PtGA/PASI/HAQ were 19[12;24]/11[8;16]/65[50;75]/70[50;80]/14.5[7;23.8]/1[0.625;1.5] accordingly. Enthesitis/Nail PsO were found in 27 pts (65.9%)/in 33 out of 41 pts (80.5%) respectively. BSA>3% was found in 20 out of 41 pts (51.3%). After 6 mo of therapy all MDA parameters as well as DAPSA score decreased significantly (table 1). The NPts with Enthesitis decreased significantly and became 12 out of 41 pts (30.8%). After 6 mo of therapy the NPts with nail PsO didn't decrease significantly compared with the BL; the dynamics was: from 33 out of 41 pts (80.5%) to 31 (79.5%) accordingly (p=0.991). MDA was found in 15 out of 41 pts (36.58%). After 6 mo of therapy no significant differences were seen between the groups of pts with/without MDA in the NPts with nail PSO: 11 out of 15 pts (73.33%) and 20 out of 24 (83.3%) accordingly (p=0.456). Enthesitis, PASI, nail PsO had a negative impact on achieving MDA, while joint symptoms and PROs were significantly associated with MDA attainment after 6 mo of TF therapy (Fig. 1 ). Conclusion: In real clinical practice TF treatment improves all MSK symptoms in active PsA pts. The presence of Enthesitis and Skin/Nail PsO severity at BL has a negative impact on MDA attainment in short-term outcomes. These findings should be taken into consideration when choosing treatment. References: [1] Kavanaugh A, Gottlieb A, Morita A, et al. Ann Rheum Dis 2019;0:1–5. doi:10.1136/annrheumdis-2018-215003 Research granted by Pfizer. Disclosure of Interests: Maria Chamurlieva: None declared, Elena Loginova Speakers bureau: Janssen, ELENA GUBAR: None declared, Yulia Korsakova: None declared, Svetlana Glukhova: None declared, Tatiana Korotaeva Grant/research support from: Pfizer, Consultant of: Abbvie, BIOCAD, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Novartis-Sandoz, Pfizer, UCB, Speakers bureau: Abbvie, BIOCAD, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Novartis-Sandoz, Pfizer, UCB